DETERMINANT FACTORS OF STUDENT STAFF WORK READINESS AT SANATA DHARMA UNIVERSITY, YOGYAKARTA (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study aims to analyze self-efficacy, academic achievement, motivation to enter the workforce and internship experience as determinants of work readiness of Sanata Dharma University student staff. The research sample consisted of 126 respondents, who were part of Sanata Dharma University student staff who worked at campus 1, 2, and campus 3. The sample selection used a purposive sampling method. The data analysis technique used Multiple Linear Regression with the help of the IBM SPSS 25 application. The results of the study showed that self-efficacy and internship experience partially had a significant effect on student work readiness, while academic achievement and motivation to enter the workforce partially had no effect on student work readiness. The findings of this study confirmed that student work readiness was determined by internal factors, namely self-efficacy and internship experience. The implications of this study on strengthening student self-efficacy through student participation in organizational activities, participating in soft skill development activities, and internship programs held by the University.
Keywords: Self-Efficacy; Academic Achievement; Motivation to Enter the World of Work; Internship Experience; Job Readiness